Mesenchymal stromal cells (MSCs): science and f(r)iction - Bieback, Karen; Wuchter, Patrick; Klüter, Harald; Ho, Anthony Dick (Journal of molecular medicine, 2012)
Due to their multi-lineage differentiation capacity, support of haematopoiesis, immunomodulation and secretion of proregenerative factors, mesenchymal stem/stromal cells (MSCs) are in the focus of intense research since decades. The literature is replete with reports on their potential in preclinical model systems. However, the heterogeneity of the primary cell population as starting material and the diverse protocols for isolation and cultivation are hampering progress in their clinical application. Consensus on common standards and harmonised isolation and characterisation protocols are important to ensure safety and efficacy. This review focuses on the recent scientific evidence of clinically relevant properties and on the speculative cardiomyogenic and hepatic differentiation potential of MSCs. Special emphasis is put on the importance of standardisation and harmonisation in clinical-scale manufacturing.
Published online: 31 May 2012
Gesehen am 25.06.2018